Beyond Rational Games: An Analysis of the "Ecology of Values" in Internet Governance Debates. (December 2013) - Powell, Alison; Nash, Vicki
<x xml:space="preserve">Abstract</x> The same characteristics that make the Internet so unique as a tool for also create concerns that dangerous and illegal content and interactions are more easily available, particularly to children. This article explores these issues by examining the debate between two long‐established strands of digital advocacy: child protection and freedom of expression. It suggests the value of a new analytic framework and model of intervention, arguing that a negotiation of values characterizes a policy development ecology. This article describes an "ecology of values" based on the phronetic, rather than epistemic, aspects of the discursive relationships created between members of these two advocacy groups, where core values are negotiated and redefined as part of the policymaking process.